ANALISIS KINERJA PEGAWAI DI KECAMATAN MARGADANA KOTA TEGAL - Noviana, Nindita Ria; Nurcahyanto, Herbasuki; Hariani, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Human resources is driving organizations to connect all his energy, mind, talent, creativity and strive for the sake of the survival of the organization. Nowdays, One thing is often still a connection problem in the relationship between people and governments in the region is in the field of public services, especially in terms of quality or service quality of government officials to the public. This study aims to determine the dimensions of what drives performance and hinder the performance of employees in the District Margadana Tegal and to analyze and describe the performance of the Civil Service in the District Margadana Tegal. This study used a qualitative descriptive method Subdistrict Margadana locus and focus research on the performance of staff members. Instruments in this study is the researchers themselves, who act as planners, implementers in collecting data, analyzing, interpreting the data and writing research reports that assisted with the interview, the informant purposive sample selection techniques. Mechanical analysis is done through reduction, data presentation and conclusion by using taxonomic analysis. Based on the survey results revealed that the overall performance of employees is not good, there are still many things that need to be repaired it can be seen from many dimensions that hinder the performance of employees in the District Margadana. The dimensions that support the performance of employees in the District Margadana is the dimension of knowledge work, cooperation dimension, the dimension of personal qualities, while inhibiting dimension is the dimension of the quantity of work, dimensions quality of work, creativeness dimensions, the dimensions of dependability, and the dimensions of the initiative. Suggestions are presented in this study is the leader should implement the target time, and more emphasis to pay more attention to and comply with existing standards work system, the leader must be able to be more open so as to create conditions that can motivate subordinates and provide comfort to employees to submit ideas , there must be strict sanctions so that a deterrent effect, and requires the employee to make the planning work and individual work schedules.